2021
DOI: 10.1088/1742-6596/1742/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mathematics Anxiety and Mathematical Problem-Solving Skill

Abstract: The purpose of this research is to analyze the correlation between mathematics anxiety and mathematical problem-solving skill. The data was collected by using a mathematics anxiety questionnaire and a problem-solving test. There were seven questions for the test of mathematical problem-solving and 25 questions for the mathematics anxiety questionnaire. The questionnaire was arranged by using the Likert Scale. The data were analyzed using the Pearson correlation formula. The population is the students in the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…The weighted average of the two variables for mathematical thinking is -0.40 (problem-solving) . The finding of this study supports the findings of Rusyda et.al [50] where it was indicated that there was a negative correlation between mathematics anxiety and mathematical problem-solving. This finding contradicts the study of Joseph [51] which found that test anxiety had almost no relationship with the mathematical problem-solving test.…”
Section: Effect Sizessupporting
confidence: 92%
“…The weighted average of the two variables for mathematical thinking is -0.40 (problem-solving) . The finding of this study supports the findings of Rusyda et.al [50] where it was indicated that there was a negative correlation between mathematics anxiety and mathematical problem-solving. This finding contradicts the study of Joseph [51] which found that test anxiety had almost no relationship with the mathematical problem-solving test.…”
Section: Effect Sizessupporting
confidence: 92%